2002
DOI: 10.1161/01.cir.0000016640.99114.3d
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Coronary Revascularization in the Elderly

Abstract: Background-Elderly patients with ischemic heart disease are increasingly referred for coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI). However, reports of poor outcomes in the elderly have led to questions about the benefit of these strategies. We studied survival by prescribed treatment (CABG, PCI, or medical therapy) for patients in 3 age categories: Ͻ70 years, 70 to 79 years, and Ն80 years of age. Methods and Results-The Alberta Provincial Project for Outcomes Assessment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(132 citation statements)
references
References 21 publications
10
113
0
9
Order By: Relevance
“…Claessen et al [7] recently report an increasing percentage of octogenarians treated with primary percutaneous coronary intervention (PCI) from 1997 to 2007, who show an increased short-and long-term mortality when compared to younger patients. This finding is in keeping with earlier clinical trials such as GISSI-2 and GUSTO-1 [8,9] as well as with previous studies in the era of mechanical revascularization by others [10][11][12][13][14][15] and us [16].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Claessen et al [7] recently report an increasing percentage of octogenarians treated with primary percutaneous coronary intervention (PCI) from 1997 to 2007, who show an increased short-and long-term mortality when compared to younger patients. This finding is in keeping with earlier clinical trials such as GISSI-2 and GUSTO-1 [8,9] as well as with previous studies in the era of mechanical revascularization by others [10][11][12][13][14][15] and us [16].…”
Section: Introductionsupporting
confidence: 91%
“…Higher comorbidities and a higher incidence of PCI failure may account for this finding. Most studies have reported that older age is associated with decreased procedural success after PCI or increased in-hospital complications [10][11][12][13][14], but data on this topic are still controversial. In a retrospective analysis, de Boer et al [27] document that PCI in octogenarians has a high technical and procedural success rate even if older age is independently associated with greater mortality after PCI for AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Careful monitoring of INR as an outpatient must be emphasized to a departing ED patient as supra-therapeutic INRs are associated with an increased risk of intracranial bleeding. Aspirin can be considered in low-risk patients who are not candidates for anticoagulation; however, it is not an equivalent substitute for warfarin [23]. The BAFTA study of patients greater than 75 years of age finds that warfarin provides a 52% reduction in risk of embolism compared to aspirin [18].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Although primary percutaneous coronary intervention (PCI) is beneficial, elderly patients with ST-elevation myocardial infarction (STEMI) still have a worse prognosis, including worse myocardial reperfusion, as compared to younger patients [1][2][3][4]. Glycoprotein (GP) IIb/IIIa inhibitors are favourable in STEMI patients [5,6], and the additional value of early pre-hospital high bolus dose tirofiban has recently been established [7,8], but combined antithrombin and GP IIb/IIIa inhibitor regimens have also been associated with a higher risk of bleeding [9,10].…”
Section: Introductionmentioning
confidence: 99%